Peran Administrasi Kurikulum dalam Meningkatkan Kualitas Pendidikan di Sekolah - Nisrina Nurul ‘Aini; Anisa Rahima; Syarifah Rodiyah (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
This research is to understand the importance of curriculum administration in improving the quality of education in elementary schools where the method is carried out using the media of literature studies where the writers collect data and materials from various related sources. that literature study is the study of data from various reference books and the results of previous research that are relevant to the research to obtain a theoretical basis from the problem to be researched. Literature study is referred to as library research or literature research. To ensure the validity of the work carried out with the following efforts: a. research; b. study of the data collection period; d. study; e. Involve the team in discussions. As a result of the study, he found that the role of curriculum administration is very important in supporting success in the world of education where both in the quality of education in the classroom, the implementation of the curriculum in schools, as well as the role of teachers in the implementation of the curriculum in the world of education in schools, which can improve and produce students who are critically creative in the world of education.